Extrusion-based additive manufacturing of functionally graded ceramics. Issue 3 (March 2021) - Li, Wenbin; Armani, Amir; Martin, Austin; Kroehler, Benjamin; Henderson, Alexander; Huang, Tieshu; Watts, Jeremy; Hilmas, Gregory; Leu, Ming
Abstract: The Ceramic On-Demand Extrusion (CODE) process has been recently proposed for additive manufacturing of dense, strong ceramic components via extrusion with uniform layered drying. This study focuses on enabling CODE to fabricate functionally graded ceramics. A controlled volumetric flowrate for each ceramic paste was used to achieve a gradient between alumina and zirconia. A dynamic mixer was built to mix constituent ceramic pastes homogeneously. Functionally graded alumina/zirconia samples were printed, sintered, and tested to examine the capability of CODE in fabricating functionally graded components. The desired and actual material compositions were compared using energy dispersive spectroscopy. Dimensions of sintered samples were evaluated to study the deformation of functionally graded components during drying and sintering. Vickers hardness was also measured at different locations, corresponding to different material compositions. Finally, a case study was conducted to demonstrate the capability of the proposed method to build functionally graded ceramics with complex geometries.